Fundamentals of entrepreneurship (ENT300) : Aerohealth fitness centre / Shaffaridzuan Yakub … [et al.] - Yakub, Shaffaridzuan; Hass, Nurhisyam; Arieff, Muhammad Benyamin; Neru, Wenny (2013)
Aerohealth Fitness Centre is a partnership company aimed to provide the customers With gymnasium services. There are five (5) members of this company partnership which consist of the General Manager, Administration Manager, Operation Manager, Marketing Manager, and Financial Manager- The major objective of our company is to provide customers m Kuching area with fitness and health centre that can fulfil their needs and demands Aerohealth Fitness Centre IS design with its different services that have not yet been offered In any fitness centre In Kuching. What makes our business so unique and different is that we offer a separate gymnasium for the men and women. We found out that most customers especially women feel that they need specific places of gymnasium for them to workout. With this new type of services we Will be able to compete and attract more customers especially among the women to our fitness centre. In addition we also provided health supplement to our customer and also with the gym instructor to advise them.